A Method to Harvest Electrical Energy from Living Plants. - Choo, Ying Ying; Dayou, Jedol (Journal of Science and Technology, 2013)
In this paper, some fundamental investigations are established to demonstrate the potential of harvesting electrical energy from living plants. The energy is harvested by embedding electrodes into the plant to allow flow of ions and hence generate electricity. Multiple random tests have been conducted using different type of electrodes and plants as an attempt to determine the characteristics of the harvesting system. It is found that voltages are produced to greater or lesser extents by all tests where combination of copper-zinc and aloe vera produces the highest voltage. In addition, it is shown in this paper its ability to light up Light Emitting Diode (LED), digital clock and calculator which grants it a potential to be used for low power electrical consumption appliances in the future.